Smart Control of Buck Converters using a Switching-based Clustering Algorithm - Abegaz, B.W.; Cmiel, M. (2019 14th Annual Conference System of Systems Engineering (SoSE), 2019)
This paper proposes a new approach to the control of switching voltage regulators (buck converters). The method is performed using a switching-based clustering algorithm. The implementations of competing approaches such as a fuzzy-logic controller, proportional integral derivative controller and a neural network based controller are presented in order to compare and evaluate the performance of the switching-based clustering algorithm. The results of the approach show that the proposed method could improve the stability and the performance of the buck converter system by 2.7% in terms of settling time and by 0.6% in terms of the overshoot value as compared to other control methods for buck converters.